2021
DOI: 10.3390/cancers13061352
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer-Associated Mesothelial Cells: Transdifferentiation to Minions of Cancer and Orchestrate Developing Peritoneal Dissemination

Abstract: Ovarian cancer has one of the poorest prognoses among carcinomas. Advanced ovarian cancer often develops ascites and peritoneal dissemination, which is one of the poor prognostic factors. From the perspective of the “seed and soil” hypothesis, the intra-abdominal environment is like the soil for the growth of ovarian cancer (OvCa) and mesothelial cells (MCs) line the top layer of this soil. In recent years, various functions of MCs have been reported, including supporting cancer in the OvCa microenvironment. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 99 publications
1
29
0
Order By: Relevance
“…The components of the tumor microenvironment include all of the nonmalignant stroma cells inside the tumor other than the tumor cells, including fibroblasts, endothelial cells, immune cells, and platelets [5,6]. Paget proposed the "seed and soil" theory in 1889 and conducted an indepth analysis of the molecular characteristics of "seeds" (cancer cells) [7][8][9][10][11]. By studying the "soil" formed by cancer cells and host immune cells, scientists found that immune cells usually bind to cancer cells and obtain specific biological phenotypes via interactions with them.…”
Section: Introductionmentioning
confidence: 99%
“…The components of the tumor microenvironment include all of the nonmalignant stroma cells inside the tumor other than the tumor cells, including fibroblasts, endothelial cells, immune cells, and platelets [5,6]. Paget proposed the "seed and soil" theory in 1889 and conducted an indepth analysis of the molecular characteristics of "seeds" (cancer cells) [7][8][9][10][11]. By studying the "soil" formed by cancer cells and host immune cells, scientists found that immune cells usually bind to cancer cells and obtain specific biological phenotypes via interactions with them.…”
Section: Introductionmentioning
confidence: 99%
“…SOC cells exfoliate as single cells or multicellular spheroids that disseminate with the peritoneal fluid flow ( Ahmed and Stenvers, 2013 ; Worzfeld et al, 2017 ; Rickard et al, 2021 ). Metastatic spread is largely mediated by the ability of spheroids, but also individual cells, to adhere to a monolayer of peritoneal mesothelial cells (MCs) resting upon a basement membrane, to induce their retraction and to penetrate the sub-mesothelial interstitial collagen-rich extracellular matrix (ECM), followed by their survival, and tumor nodule formation with surrounding host cells ( Burleson et al, 2004 ; Shield et al, 2009 ; Mogi et al, 2021 ). In this context, the invasive behaviour of SOC spheroids depends upon their contractile capacity and involves both integrins and cadherins ( Sodek et al, 2009 ; Iwanicki et al, 2011 ; Klymenko et al, 2017a ; Klymenko et al, 2017b ; SacksSuarez et al, 2019 ; Goyeneche et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although for many years mesothelial tissue has been considered as a sheet of cells with low mobility, serving as a barrier against tumors, recent studies demonstrated that they can be reprogrammed by TME to acquire invasive properties and tumor-supporting functions, mainly in the advanced stages of SOC tumor, which is likely to develop peritoneal dissemination ( Rynne-Vidal et al, 2015 ; Mogi et al, 2021 ). MCs might be altered by SOC cells through the stimulation of soluble factors present in ascites ( Matte et al, 2014 ; Matte et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…OvCa cells released and floating in ascites have metastatic potential to the peritoneum 11 . The amount of tumor cells in the peritoneum, which is dependent on the total tumor mass in the peritoneum, is associated with the positivity rate on cytology.…”
Section: Discussionmentioning
confidence: 99%